Ablative Volume of Radiofrequency Ablation Related to Intrahepatic Recurrence-Free Survival of Hepatocellular Carcinoma - Nakarin Inmutto; Siripong Thaimai; Tanop Srisuwan; Thanate Kattipathanapong; Natthaphong Nimitrungtawee (The Arab Journal of Interventional Radiology, 2021)
Purpose The aim of this study was to evaluate intrahepatic recurrence-free survival of hepatocellular carcinoma (HCC) after Radiofrequency ablation (RFA) Methods A retrospective cohort study of single HCC treated by RFA between 2015 and 2017. Fifty patients were enrolled in the study. Tumor volume and ablative volume were measured by using Syngo.via application (Siemen Healthineers, United States). Ablative volume classified into small and large ablative volumes. Ablative margin was evaluated by visual comparison between pre- and post-RFA images and classified into two groups: closed ablative margin (<0.5cm) and large ablative margin (>0.5 cm). The recurrence tumor was classified as local tumor progression (LTP) and intrahepatic distant recurrence (IDR). The recurrence-free survival rate and independent risk for tumor recurrence were analyzed. Results Recurrence-free survival rate at the first, second, third, and fourth year after RFA was 83, 56, 44, and 44%, respectively. The average recurrence-free survival time in large ablative volume group was significantly longer than small ablative volume group (31.57 vs. 8.50 months, p = 0.003). A significant independent risk factor for tumor recurrence was large ablative volume (hazard ratio = 0.12, 95% confidence interval = 0.02–0.84, p = 0.033). The IDR group had ratio of actual ablative volume by ideal ablative volume (ablative ratio) higher than LTP group and nonrecurrent group. Conclusion The large ablative volume prevented tumor recurrence and increased recurrence-free survival rate. But aggressive ablation with high ablative volume ratio could increase risk of IDR.